2023
DOI: 10.3390/mi14010209
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Anticandidal Activities of Greenly Synthesized ZnO Nanomaterials with Commercial Antifungal Agents against Candidal Infections

Abstract: The high occurrence of mycological resistance to conventional antifungal agents results in significant illness and death rates among immunodeficient patients. In addition, the underprivileged therapeutic results of conventional antifungal agents, besides the potential toxicity resulting from long term therapy necessitate the fabrication of efficient antimicrobial combinations. Hence, the objective of the present investigation is to synthesize, characterize and investigate the anticandidal action of green zinc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Conversely, ZnO-NPs have the ability to oxidize crucial cellular components of candidal cells owing to the action of ROS, including DNA and proteins. This process ultimately leads to the initiation of cell death in the fungus [ 84 ]. In addition, synergistic anticandidal effectiveness of ZnO-NPs with nystatin antifungal agent was observed against C. tropicalis and C. glabrata stains, with relative IFA values of 1.06 and 2.39, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, ZnO-NPs have the ability to oxidize crucial cellular components of candidal cells owing to the action of ROS, including DNA and proteins. This process ultimately leads to the initiation of cell death in the fungus [ 84 ]. In addition, synergistic anticandidal effectiveness of ZnO-NPs with nystatin antifungal agent was observed against C. tropicalis and C. glabrata stains, with relative IFA values of 1.06 and 2.39, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The cytotoxicity results were consistent with those of a prior investigation, which reported an IC 50 value of 238 µg/mL for Vero cells after a 72 h incubation period with ZnO-NPs synthesized using Pichia kudriavzevii extract as a green method [ 40 ]. A previous study reported a relatively low IC 50 value for the phytosynthesized ZnO-NPs against WI-38 cells, with an average IC 50 of 642.21 μg/mL [ 84 ]. According to the US Food and Drug Administration (FDA), it is recommended that zinc oxide nanoparticles be regarded as safe, specifically falling under the category of generally recognized as safe (GRAS) [ 91 , 92 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among the phyto-synthesized metal oxide nanoparticles, zinc oxide; ZnO has great consideration for its peculiar chemical and thermal stability 9 , biocompatibility 10 , selectivity, and cytotoxic activity against cancerous cells 11 . Accordingly, they have been recently used in numerous biomedical and pharmacological applications, such as antibacterial, antioxidant, anticancer, antifungal, and antidiabetic applications 12 15 . Moreover, studies have reported ZnO NPs as an alternative emergent tool successfully utilized for water disinfection against numerous microbial strains such as Aspergillus flavus, Escherichia coli, Candida albicans, and Staphylococcus aureus 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, Zn(II) ions in corresponding salt solutions can be reduced, capped, and oxidized to form stable and well-dispersed ZnO NPs using plant extracts [ 22 ]. Several studies have used plant extracts to biosynthesize green zinc oxide nanomaterials with photocatalytic and antibacterial properties [ 23 ]. For instance, flower-like ZnO structures with hexagonal wurtzite forms were produced using Arabic Gum (AGZnO) or Karaya Gum (KGZnO) with crystallite sizes of 20 and 19 nm, respectively.…”
Section: Introductionmentioning
confidence: 99%